2003
DOI: 10.1136/pmj.79.933.397
|View full text |Cite
|
Sign up to set email alerts
|

Single megadose vitamin A supplementation of Indian mothers and morbidity in breastfed young infants

Abstract: Background and objective: In developing countries low maternal vitamin A stores combined with increased demands of pregnancy and lactation may lead to its deficiency in breastfed infants. This study evaluates the effects of maternal supplementation with a high dose of vitamin A on the serum retinol levels of exclusively breastfed infants, and their morbidity in the first six months of life. Setting: Hospital based. Study design: Randomised controlled trial. Subjects and methods: Mothers of the test group (n=15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
12

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 22 publications
2
43
0
12
Order By: Relevance
“…The magnitude of the effect of supplementation with either retinol or b-carotene on breast milk retinol concentrations has been highly variable as reported by nine randomized controlled trials in presumably HIV-uninfected women (Stoltzfus et al, 1993;Roy et 1999; Vinutha et al, 2000;Canfield et al, 2001;Muslimatun et al, 2001;Bahl et al, 2002;Basu et al, 2003;Dijkhuizen et al, 2004) and one randomized controlled trial in HIVinfected Malawian women (Semba et al, 2000). This variation likely depends on differences in the dose and timing of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the effect of supplementation with either retinol or b-carotene on breast milk retinol concentrations has been highly variable as reported by nine randomized controlled trials in presumably HIV-uninfected women (Stoltzfus et al, 1993;Roy et 1999; Vinutha et al, 2000;Canfield et al, 2001;Muslimatun et al, 2001;Bahl et al, 2002;Basu et al, 2003;Dijkhuizen et al, 2004) and one randomized controlled trial in HIVinfected Malawian women (Semba et al, 2000). This variation likely depends on differences in the dose and timing of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Stoltzfus et al (1993) observed higher serum retinol levels and fewer inadequate RDR in 6-month-old infants whose mothers had received 300 000 IU vitamin A 1-3 weeks after delivery compared with controls. In two Indian studies (Vinutha et al, 2000;Basu et al, 2003), significantly higher serum retinol levels were observed in 3-month-old infants whose mothers were supplemented with 200 000 IU vitamin A immediately after delivery compared with the placebo group. It is difficult to explain these differences in relation to our findings simply on the basis of socioeconomic conditions as all the cited studies were conducted on lowincome populations.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin A supplementation has many advantages for the baby, as it provides adequate amounts of vitamin A on a daily basis through mother's milk, thus being considered the safest form of supplying this vitamin to newborn babies (Basu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The foetus is totally dependent on the mother for the supply of nutrients essential to maintain its life. An optimal maternal nutritional status has been shown to reduce the risks of a preterm birth and low birth weight (1)(2)(3) , improve postnatal growth (4,5) , and reduce both maternal and infant morbidity and mortality (6)(7)(8)(9) . Despite a trend of improved infant growth in most countries due to enhanced intakes of macronutrients (10) , a low maternal nutritional status during the critical stage of foetal development subsequently contributes to growth retardation in the offspring and adverse health outcomes in later life (11) .…”
mentioning
confidence: 99%